Bionomic Assessment of the Marine Fisheries in the Northern Coast of Central Java - Kuntjoro, Kusumo Djoko (1986)
The Central Java fishing industry has been operated for decades under the policy of open access management. Present fishery policy in the area emphasizes resource development in order to improve the fishing industry. However, development programmes place some pressure on the resource use that could lead to depletion. This study was undertaken to evaluate the status of the fisheries resource utilization of the northern coast of Central Java. Temporal or static fishing models were used to assess maximum and economic sustainable yields. Multiple input models of Schaefer and Fox were used but failed to produce the expected results. However the single model of Schaefer was able to do so. Results of the static single input model analysis showed that the fisheries resource were, in fact, highly exploited. The actual effort nearly approaches the estimated effort for Maximum Sustainable Yield. However, the existing effort was far higher than the estimated effort for the Open Access Equilibrium. The fact that the fishermen still continue fishing while economic rent had already dissipated, indicates that they were forced to do fishing. This could be due to the absence of alternative incomes sources for them. Evaluation of the Central Java marine fisheries development programmes using Smith's Table of effect on the development on traditional fisheries showed that rural development method for alternative incomes sources (the appropriate development method to increase fishermen's income) received little attention. Therefore, this method is strongly recommended. The specific programmes recomended are development of the backward and forward-linkages of the fishing industry, the establishment of other rural industries which creates employment and generates income to local fishermen and out-migration of local fishermen to less-populated islands in Indonesia.